REGULATION OF RADIO FREQUENCY SPECTRUM AND ITS IMPLEMENTATION CHALLENGES IN THE PERSPECTIVE OF INTERNATIONAL LAW - Jean Claude Geofrey Mahoro; Agus Pramono (Fakultas Hukum, Universitas Diponegoro, 2019)
The radio frequency spectrum is a limited natural resource, which is very important and strategic in the operation of telecommunications. Considering that it is a limited natural resource, its management is regulated internationally by the International Telecommunication Union (ITU), in which details are set out in the radio regulations (RR) as an integral part of the ITU Convention. The study is based on applicable legal regulations and is supported by literature studies. The results of the study indicate that the regulation of the radio frequency spectrum is based on radio regulations, international agreements within the ITU through the World Radio communication Conference forum. The implications of regulating the use of the radio frequency spectrum always take into account the general public needs for the dynamics of the progress in telecommunications technology, of which implementation of its utilisation rests in the principle of fairness and equity between regions, and efficiency. Therefore, all policies made are directed at creating a market balance, ensuring fair competition between telecommunication operators as a potential to prevent market dominance, as well as protecting consumers.